Primary evaluation of resistance to the root-mealybug Dysmicoccus texensis in Coffea canephora clones resistant to Meloidogyne spp - Fatobene, Bárbhara Joana dos Reis; Guerreiro Filho, Oliveiro; Gonçalves, Wallace (Coffee Science - ISSN 1984-3909, 2012)
The purpose of this paper was to investigate the coffee plants variability to the resistance to root-mealybugs,Dysmicoccus texensis, and the root-knot nematodes Meloidogyne. These species are considered important threats to coffeeplantations, especially in the main producing regions of São Paulo, as Alta Mogiana and Alta Paulista. The interaction among D.texensis and seven selected C. canephora clones that express resistance to different Meloidogyne species were evaluated inexperiments under greenhouse, regarding the differences in the infestation standards presented by clones. Mealybugs reproductionin roots of clones IAC 5, EH 5, EH 7, EH 101 and EH 199 was significantly reduced, suggesting the possibility of finding multipleresistance to the biotic stress.